Effect of mooring line properties and fairlead slopes on the restoring behavior of offshore mooring system - Montasir, O.A. (Maxwell Science Publications, 2014)
Mooring lines are used as station keeping systems for the deep-water floating offshore platforms. Mooring lines have considerable effect on the project overall cost. Therefore, it is necessary to economize their cost by choosing appropriate material and configuration which, in turn give the required responses for the platform by possessing good restoring capability. Hence, a numerical study has been conducted on the restoring behavior of the mooring system for different mooring line materials, line diameters and fairlead slopes. Two mooring systems consisting of mooring lines arranged unsymmetrical were considered. Assuming the drag forces on the mooring lines to be negligible and the change in the line geometry as insignificant, the mooring system has been analyzed using the quasi-static analysis. The numerical model thus developed has been validated using experimental model test data and a parametric study was conducted using the parameters mentioned. It can be concluded that the polyester mooring lines provide better restoring forces compared to the other materials and also the behavior of mooring system can be greatly affected with change in line diameter and fairlead slope. Â© Maxwell Scientific Organization, 2014.